Languages of art: An approach to a theiry of symbols - Goodman, Nelson (Sussex The Harvester Press, 1968)
"Like Dewey, he has revolted against the empiricist dogma and the Kantian dualisms which have compartmentalized philosophical thought. . . . Unlike Dewey, he has provided detailed incisive argumentation, and has shown just where the dogmas and dualisms break down." -- Richard Rorty, The Yale Review« Minder